ON An Infra-\(α\)-Open Sets - Othman, Hakeem; Page, Md.Hanif. (Global Journal of Mathematical Analysis, 2016)
In this paper, we define a new class of set in general topology called an infra- \(α\) open set and we investigate fundamental properties by using this new class. The relation between infra-\(α\)-open set and other topological sets are studied.Moreover, In the light of this new definition, we also define some generalization of continuous mappings and discuss the relations between these new classes of mappings and other continuous mappings. Basic properties of these new mappings are studied and we apply these new classes to give characterization of connected space.